Influencia de la proporción y concentración del coagulante cactus nopal en la clarificación de aguas del rio Moche para riego - Lecca Malo, Sarai Esther (2023)
In the present investigation, the objective was to determine the influence of the proportion and concentration of the natural coagulant obtained from the nopal cactus on turbidity, total suspended solids, pH and the efficiency of the clarification of the waters of the Moche River for drip irrigation. For this, an experimental, applied investigation was carried out, the population was constituted by the waters of the Moche River located in the city of Trujillo, which has an approximate flow of 8.8 m3/s in summertime and the sample will be collected in a timely manner. near the Moche district at a strategic point on the Moche River, it consists of 80 liters of water collected from the Moche River in a properly sterilized bucket. The independent variables were the concentration of natural coagulant at 30 mg/L and 40 mg/L and the ratio of aluminum sulfate to natural coagulant at 10%-90%, 30%-70%, and 50%-50%. Concluding that the proportion and concentration of the natural coagulant obtained from the nopal cactus positively influences turbidity, total suspended solids, pH and efficiency, achieving greater clarification of the waters of the Moche River to be used for drip irrigation.